Key trends and practices in diaspora education policy-making: Comparative analysis of three countries: Poland, Lithuania and Hungary - Anzhela Popyk (University of Warsaw, Centre of Migration Research (CMR), 2022)
Education policy constitutes a substantial part of the diaspora policies in Poland, Lithuania and Hungary. Though, the main aim of the education policy for diaspora is to establish ties with the diaspora members by ensuring access to the native language learning, transmitting the home country's history, preserving culture and traditions. These pursue the superior purpose of bringing up ethnic identity and national awareness. This report evaluates and compares the diaspora education policies across three countries, with a spotlight on the post-accession emigration groups. The analysis indicates that Polish, Lithuanian and Hungarian education policies are built on formal and non-formal types of education, with little space for informal learning. Besides, the report showcases, the selectiveness of the policies in terms of ethnic and age groups of the diaspora. The paper ends with the suggestion on the directions to modify the educational policy towards making it more exhaustive by strengthening various forms of education.
Keywords: 330; diaspora; diaspora policy; education; Poland; Lithuania; Hungary